Commons-Based Peer Production in the Work of Yochai Benkler - Vangelis Papadimitropoulos (tripleC: Communication, Capitalism & Critique)
Yochai Benkler defines commons-based peer production as a non-market sector of information, knowledge and cultural production, which is not treated as private property but as an ethic of open sharing and co-operation, and is largely enhanced by the Internet and free/open source software. This paper makes the case that there is a tension between Benkler’s liberal commitments and his anarchistic vision of the commons. Benkler limits the scope of commons-based peer production to the immaterial production of the digital commons, while paradoxically envisaging the control of the world economy by the commons. This paradox reflects a deeper lacuna in his work, revealing the absence of a concrete strategy as to how the immaterial production of the digital commons can connect to material production and control the world economy. The paper concludes with an enquiry into some of the latest efforts in the literature to fill this gap.